Academic and commercial genetic testing laboratories: complementary if not complimentary. (November 2007) - Strom, Charles M
The new century has introduced a myriad of changes in the practice of clinical and laboratory genetics. As molecular diagnostics entered the mainstream of current medical practice, a number of academic genetic laboratories faced intense financial pressure and many succumbed. Although the entry of commercial laboratories into the genetic testing arena is one factor in this process, it is by no means the only one. Increased regulatory requirements, changes in funding sources for academic institutions, and the rise of large managed care organizations also have culpability. Many academic laboratory directors have expressed hostility toward commercial laboratories, both vocally at genetic meetings and in publications. This vitriol serves no one. Commercial laboratories are here to stay and, in fact, provide important services to American healthcare consumers by making esoteric molecular diagnostic testing widely available. Rather than throw stones at each other, it is time for academic and commercial laboratories to coexist and realize that each has strengths and, most importantly, that patients are best served by cooperation, not confrontation between these equally competent groups. This article examines the historical antecedents to the current conflictive situation and offers suggestions for collaborative efforts in the future.